Teaching English or Teaching the West? Multimodal Cultural Imperialism in Big Show Level 5 Textbooks Used in Indonesian Islamic Montessori Schools - Muhammad Arif; Qurrata’ain; Greis Evalinda; Ida Nyoman Tri Darma Putra (Universitas Islam Negeri Palopo, 2026)
This study extends Critical Discourse Analysis (CDA) beyond traditional textual examination to investigate multimodal representations of culture in